First-Principles Study of Chemical Mixtures of CaCl(2) and MgCl(2) Hydrates for Optimized Seasonal Heat Storage - Pathak, A. D. (J Phys Chem C Nanomater Interfaces, 2017)
[Image: see text] Chloride-based salt hydrates form a promising class of thermochemical materials (TCMs), having high storage capacity and fast kinetics. In the charging cycles of these hydrates however hydrolysis might appear along with dehydration. The HCl produced during the hydrolysis degrades and corrodes the storage system. Our GGA-DFT results show that the enthalpy charge during proton formation (an important step in hydrolysis) is much higher for CaCl(2)·2H(2)O (33.75 kcal/mol) than for MgCl(2)·2H(2)O (19.55 kcal/mol). This is a strong indicator that hydrolysis can be minimized by appropriate chemical mixing of CaCl(2) and Mg Cl(2) hydrates, which is also confirmed by recent experimental studies. GGA-DFT calculations were performed to obtain and analyze the optimized structures, charge distributions, bonding indicators and harmonic frequencies of various chemical mixtures hydrates and compared them to their elementary salts hydrates. We have further assessed the equilibrium products concentration of dehydration/hydrolysis of the chemical mixtures under a wide range of operating conditions. We observed that chemical mixing leads to an increase of the onset hydrolysis temperature with a maximum value of 79 K, thus increasing the resistance against hydrolysis with respect to the elementary salt hydrates. We also found that the chemical mixing of CaCl(2) and MgCl(2) hydrates widens the operating dehydration temperature range by a maximum value of 182 K (CaMg(2)Cl(6)·2H(2)O) and lowers the binding enthalpy with respect to the physical mixture by ≈65 kcal/mol for TCM based heat storage systems.